STUDI LITERATUR: Faktor Kualitas Pelayanan terhadap Loyalitas Pasien di Rumah Sakit Indonesia - Purnama, Engga; Yuliaty, Farida (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to examine the service quality factors that influence patient loyalty in Indonesian hospitals. Service quality is a crucial aspect in maintaining and enhancing patient trust and loyalty. This literature review identifies five key dimensions of service quality: reliability, responsiveness, assurance, empathy, and tangibles. Each dimension plays a significant role in shaping patient loyalty, through consistent service delivery, quick responses, medical staff competence, personal attention, and the quality of physical facilities. Several studies indicate that patient satisfaction also acts as a mediator between service quality and loyalty, good service increases satisfaction, ultimately affecting patient loyalty. Amid the intense competition in healthcare services in Indonesia, optimal service quality is a key factor in patient retention. Therefore, hospital management must focus on each service quality dimension to create a satisfying patient experience. The findings of this review are expected to guide hospitals in developing effective strategies for improving service quality to retain and increase patient loyalty.